The Material Culture of The Urban Site Sesc Ver-O-Peso, in Belém, at The Amazon: Possibilities of Analyses (Global Journal of Human-Social Science, 2023)
Starting from the material culture excavated at the Sesc Ver-o-Peso site in the historic center of Belém do Pará, I propose to analyze the archaeological remains from their attributes and combine this analysis with other possibilities of perceiving the digger materials. Fragments and pieces of stoneware, glass, metal, and other materials were analyzed based on pre-defined common attributes of historical archaeology. Still, the results of the analyses were discussed and problematized based on a broader understanding of the meanings of material culture and its impacts on people. In addition to the already familiar information regarding chronologies and habits of use of glassware and other domestic material cultures, reflecting from researchers such as Latour, for whom the object is an active actor in building society, it was possible to problematize the historical archaeology of Belém unprecedentedly. One of the conclusions expressed is that in addition to serving to tell stories that may have passed unobserved by the documents of times, material culture is also a reflection of society, actively building social life 1 .
Keywords: material culture; historical archaeology; historic city centre of belém; amazonian archaeology